2020
DOI: 10.1021/acs.jafc.0c01306
|View full text |Cite
|
Sign up to set email alerts
|

Accomplished High-Resolution Metabolomic and Molecular Studies Identify New Carotenoid Biosynthetic Reactions in Cyanobacteria

Abstract: Cyanobacteria and microalgae are characterized by a rich and varied profile of chlorophyll (8–20 mg/g) and carotenoid (>2.2 mg/g) pigments, being noteworthy material for natural pigment production in the food industry. We propose a systematic workflow that uses high-performance liquid chromatography (HPLC) coupled with high-resolution tandem mass spectrometry in a broadband collision-induced dissociation mode (bbCID) acquisition mode to simultaneously obtain MS and MS n spectra. Metabolomic studies showed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In this context, Nascimento et al (2020) reported the relative area of limonene of 0.43% in microalgae Phormidium autumnale (phylogenetically similar to Desertifilum spp.) (Nörnberg et al, 2021;Maroneze et al, 2020) and 0.32% in the microalgae Scenedesmus obliquus, result similar to this study for the microalgae Desertifilum spp. in the first case and for the microalgae Spirulina sp.…”
Section: Resultssupporting
confidence: 90%
“…In this context, Nascimento et al (2020) reported the relative area of limonene of 0.43% in microalgae Phormidium autumnale (phylogenetically similar to Desertifilum spp.) (Nörnberg et al, 2021;Maroneze et al, 2020) and 0.32% in the microalgae Scenedesmus obliquus, result similar to this study for the microalgae Desertifilum spp. in the first case and for the microalgae Spirulina sp.…”
Section: Resultssupporting
confidence: 90%
“…To increase the reliability of data in the case of metabolite profiling/targeted metabolomics, where (tentative) identification of pigments is the aim, the acquisition of MS in a highresolution mode, in combination with tandem MS, is almost a pre-requisite. This combination of working conditions and online experiments allows the analyst to obtain different pieces of information that are conveniently arranged in pairs of independent and orthogonal data of physicochemical properties, facilitating the implementation of workflow protocols for the characterization of chlorophyll and carotenoid metabolic profiles tailored to the selected strategy implemented in the study (targeted metabolomics, fingerprinting, or metabolite profiling) [85].…”
Section: Technologies: Instrumental Techniques For the Acquisition Of Spectroscopic And Spectrometric Datamentioning
confidence: 99%
“…This overall approach, although highly informative and practical, could become difficult to apply as a routine method. Lastly, metabolomics is a common and useful approach for identification purposes [57,85,179,180] and the detection of food processing [71,181,182] In addition to all of these applicability areas, pigment metabolomics has also been applied to the investigation of human health. This is possible thanks to the fact that the concept of health status has moved from just "a state" to "the ability to adapt", which was denoted as phenotypic flexibility.…”
Section: Application In Physiologic and Molecular Biology Studiesmentioning
confidence: 99%